2011
DOI: 10.3733/ca.v065n01p14
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the seasonal and reproductive biology of olive fruit fly is critical to its management

Abstract: The data is being used to develop models that will better predict when the adults are active and olives are at risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
12
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 15 publications
3
12
0
Order By: Relevance
“…B. oleae was previously recovered from overwintered fruit collected in coastal regions (Yokoyama et al 2006, Burrack et al 2011, but not in the interior valleys. Avidov (1954) reported that adult B. oleae are inactive below 16.7ЊC.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…B. oleae was previously recovered from overwintered fruit collected in coastal regions (Yokoyama et al 2006, Burrack et al 2011, but not in the interior valleys. Avidov (1954) reported that adult B. oleae are inactive below 16.7ЊC.…”
Section: Discussionmentioning
confidence: 99%
“…In CaliforniaÕs coastal and interior olive growing regions, adult B. oleae have been caught in baited traps throughout the year, although in relatively low numbers during the winter and spring seasons (Yokoyama et al 2006, Burrack et al 2011). This current study shows that B. oleae can indeed survive and overwinter as an adult in CaliforniaÕs interior valley; female ßies held in Þeld cages beginning in October survived up to 273 d (until June the following year) when supplied with food and water ( Table 1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in the S3 station inwards away from the influences of the ocean, the pre-imaginal stages were not observed until early September, and the summer genera-tion is not registered. [14] reported that weather conditions significantly affect the course of the growing season of the olive and consequently the bio-ecology of the pest Bactrocera oleae. Indeed, climate conditions change between the different study sites, especially as it approaches the coast.…”
Section: Discussionmentioning
confidence: 99%
“…Daane and Johnson (2010) reviewed the olive fruit ßy control literature and included studies of the pest in California. The distribution of olive fruit ßy in different olive production regions of the state has been delineated with trapping programs (Burrack et al 2011) and different trapping techniques . In general, high populations of olive fruit ßy occur in cool, humid coastal areas, and low numbers of the pest are found in the hot, arid areas of California, such as the San Joaquin Valley where olives are grown for canning.…”
mentioning
confidence: 99%